Asuhan Keperawatan Pada Nn. C Dengan Apendisitis Di Ruang Rawat Inap Bedah Rsud Prof.H.M.Yamin, S.H Pariaman - Sarifah Hasanah; Linda Marni; Hilma Yessi; Debby Silvia Dewi (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Appendicitis is an inflammatory condition of the appendix caused by irritation and infection of the appendiceal wall as a result of obstruction in the lumen. The Indonesian Health Survey (SKI) reported that in 2023 there were 621,435 cases of appendicitis in Indonesia. Medical record data at Prof. H. M Yamin, S.H Pariaman Regional Hospital showed that the number of patients with appendicitis in 2025 was 88 cases. The purpose of this case study was to obtain an overview of the implementation of nursing care for patients with appendicitis and to improve students’ ability to provide nursing care for patients with appendicitis in the Surgical Inpatient Ward of Prof. H. M Yamin, S.H Pariaman Regional Hospital in 2026. The method used was a case study including interviews and observations conducted in the Surgical Inpatient Ward of Prof. H. M Yamin, S.H Pariaman Regional Hospital for 5 days, from February 8 to February 12, 2026, with the sample being Ms. C diagnosed with appendicitis. The results of the case study identified five nursing problems: acute pain, hyperthermia, anxiety, impaired physical mobility, and risk of infection. Nursing interventions carried out included pain management, hyperthermia management, anxiety reduction, mobilization support, and infection prevention. Evaluation obtained during the 5 days showed that all nursing problems, namely acute pain, hyperthermia, anxiety, impaired physical mobility, and risk of infection, were resolved so that the patient was allowed to go home. Patients are advised to maintain a balanced, high-fiber nutritious diet and comply with treatment recommendations to accelerate recovery and prevent complications.